Implementation of a Differentiated Instruction Initiative: Perspectives of Leaders - Whitley, Jessica; Duquette, Cheryll; Gooderham, Suzanne; Elliott, Catherine; Orders, Shari; Klan, Amy (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2021)
Differentiated Instruction (DI) is a framework that supports planning for diversity within K-12 classrooms. Research has grown steadily over the past 15 years that explores DI implementation, as well as beliefs and practices. Literature to date has focused heavily on the experiences of educators, with limited attention given to the role of leadership in implementing DI in schools. The current study explores the perspectives of 19 school and board-level administrators regarding the ways in which a differentiated instruction framework was implemented within their school board as well as facilitators and barriers to the implementation and uptake of the framework. Interviews revealed five themes: a) DI continuum, b) differentiated professional learning supports, c) making space for shared professional learning, d) align/integrate/embed, and e) multi-level leadership. Our findings reflect a strong belief system of most of the participants with respect to the foundations of DI as well as an understanding of effective approaches to professional learning and school change.